Complete the square to rewrite the equation in the form (x−h)2=p.
x2+12x+23=0
What is the equation in (x−h)2=p form?
(x+6)2=−23
(x−6)2=−59
(x−6)2=23
(x+6)2=13

Respuesta :

Answer:

The answer to your question is  the last option  (x + 6)² = 13

Step-by-step explanation:

Data

                             x² + 12x + 23 = 0

Process

1.- Subtract 23 in both sides

                           x² + 12x + 23 - 23 = -23

2.- Simplify

                          x² + 12x + (     )   = - 23

3.- Complete the perfect square trinomial

                         x² + 12x + (6)² = -23 + (6)²

4.- Factor

                         (x + 6)² = -23 + (6)²

5.- Simplify

                         (x + 6)² = -23 + 36

6.- Result

                        (x + 6)² = 13                              

ACCESS MORE